Layanan Informasi dengan Menggunakan Media Power Point dalam Meningkatkan Aktifitas Siswa pada Layanan BK Di SMP N 1 2 X 11 Kayu Tanam Padang Pariaman - Darmailis Darmailis; Edriagus Saputra; Wisda Rahmadinur (Institut Agama Islam Sumatera Barat, 2021)
This research is a classical service action research planning, action, observation and reflection. The benefits of this research are:First, for authors to increase knowledge and be able to apply powerpoint media in implementing information services. Second, for students it is beneficial to increase student activeness in BK services. Third, it is useful for schools as input of knowledge and can apply powerpoint media in carrying out information services to students as well as being taken into consideration in developing programs to improve the learning process at a later stage.The subjects of this study were students of class VII.5 SMP N 1 2 x 11 Kayutanam in the 2019/2020 school year. The number of students who became the research subjects was 21 people consisting of 8 male students and 13 female students.The results of this study show that there is an increase in student activeness in classical services in the classroom where in the pre-cycle only 21 students asked questions with a percentage of 19.05%.In cycle 1, meeting 1, there was an increase of 3 more people, namely to 8 people who were well active, and the second meeting in cycle 1 was 8 people, so there was still less target here, then continued with the second cycle as well as 2 meetings, meeting 1 there were 14 students who immediately asked, at the second meeting there were 18 students out of 21 who were already active in the implementation of classical services with a percentage of 85.71%.So it can be concluded, that student activity can be increased through information counseling services using powerpoint media.